Kapasitas Anggota Kelompok Tani dan Regenerasi Petani - Irnawati Irnawati; Siti Aisa Lamane; Muh Zainal S (Jurnal Sosial Ekonomi Pertanian, 2023)
This study aims to analyze the factors that affect the capacity of farmer group members and farmer regeneration. Data collection is carried out by survey method and using questionnaires. The population is the heads of families who are members of farmer groups and farm youth who continue their parents' farming which amounts to 934 people. The sample amounted to 90 respondents divided by a sample of 45 respondents for members of farmer groups and 45 respondents for young farmers. Data analysis using Smart Partial Least Square (Smart PLS) Software. The results showed that age and experience of farming had a direct but not significant positive effect on the capacity of farmer group members. The role of extension workers as consultants and mentors has a direct and significant positive effect on the capacity of farmer group members. Age and farming experience negatively affect farmer regeneration. Farmer regeneration is positively influenced directly but insignificantly by the role of extension workers as influential consultants and mentors. Meanwhile, the capacity of group members has a direct and significant positive effect on farmer regeneration. The results showed that the capacity of farmer group members was influenced by the role of agricultural extension workers. Meanwhile, farmer regeneration is influenced by the capacity of farmer groups and the role of extension workers, although it does not have much influence. Keywords:    Agricultural extension; the capacity of farmer's groups; characteristics of farmers; regeneration of farmers.